The Didache : its Jewish sources and its place in early Judaism and Christianity - Sandt, Hubertus Waltherus Maria van de, 1946- (Compendia Rerum Iudaicarum ad Novum Testamentum, 2002)
This volume demonstrates that we should understand nascent Christianity and early Judaism as sharing to a large extent the same traditions. It throws fresh light on the Jewishness of the Two Ways teaching in Didache 1-6 as it presents a cautious reconstruction of the Jewish prototype of the Two Ways and traces the Jewish life situation in which the instruction could flourish. In the field of liturgical studies, a significant contribution is made to the discussion of Didache 7-10. It improves our understanding of the Jewish provenance and historical development of Baptism and Eucharist. The book also presents an intriguing look into the ministry of itinerant apostles and prophets (Didache 11-15) considering the larger environment of Jewish religious and cultural history.